Sistem Pendukung Keputusan untuk Deteksi Dini Faktor Risiko Stunting pada Ibu Hamil dengan Metode SAW - Poernareksa, Dwidya; Wardhina, Faizah; Hasanah, Uswatun; Ramadhaningsih, Ledy (LPPM STT Terpadu Nurul Fikri, 2026)
Stunting remains a critical public health challenge in Indonesia, with a prevalence of 21.5% according to the 2023 Indonesian Health Survey. The nutritional status of pregnant women is a pivotal factor in the prevention. This study aims to implement a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assess the risk of Chronic Energy Deficiency (CED) in pregnant women as a proactive measure to prevent stunting. The research analyzed data from 70 pregnant women at a public health center (Puskesmas) using four clinical criteria: height (10% weight), body weight (20%), Mid-Upper Arm Circumference/MUAC (45%), and hemoglobin levels (25%). Data were collected through observation, interviews with healthcare professionals, and ANC medical record documentation, subsequently processed using the SAW algorithm for risk ranking. The implementation results identified 54 women (77.14%) at low risk, 13 (18.57%) at moderate risk, and 3 (4.29%) at high risk. The system was evaluated using a confusion matrix, which yielded a high accuracy of 96%. This system can be integrated into primary healthcare centers (Puskesmas) and integrated healthcare posts (Posyandu) to facilitate precise and rapid interventions for CED risks, effectively replacing traditional manual processes.